1986
DOI: 10.1111/j.1348-0421.1986.tb00925.x
|View full text |Cite
|
Sign up to set email alerts
|

Mycobacterium fortuiturn Subspecies acetamidolyticum, a New Subspecies of Mycobacterium fortuiturn

Abstract: Mycobacterium fortuitum subspecies acetamidolyticum is a new subspecies of M. fortuitum and has an intermediate growth rate. It is a nonphotochromogenic mycobacterium. It does not utilize glutamate but utilizes acetamide as a simultaneous nitrogen and carbon source. It is able to utilize acetate, malate, pyruvate, fumarate, glucose, fructose, and n-propanol as the sole sources of carbon in the presence of ammoniacal nitrogen, but does not utilize them in the presence of glutamate-nitrogen. It is easily differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
7
0

Year Published

1986
1986
2019
2019

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 15 publications
1
7
0
Order By: Relevance
“…It is suggested that this organism is not a simple mutant of M. fortuitum but is a definitively different organism. The fact that this organism has a unique mycolic acid pattern supports this concept (31).…”
Section: Discussionsupporting
confidence: 49%
See 3 more Smart Citations
“…It is suggested that this organism is not a simple mutant of M. fortuitum but is a definitively different organism. The fact that this organism has a unique mycolic acid pattern supports this concept (31).…”
Section: Discussionsupporting
confidence: 49%
“…acetamidolyticum was clearly distinguished from all the other species by the present study. In a previous study, this taxon was considered to be distinct by phenetic analysis and mycolic acid analysis (31). However, it was not differentiated from M. fortuitum by DNA hybridization study and thus it was included in the species of M. fortuitum (31).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…acetamidolyticum from M. fortuitum subsp. fortuitum strains which differ in traditional clinical diagnoses, including mycolic acid patterns (50), nor can it differentiate species within the M. tuberculosis complex (MTBC) or the M. avium complex (51). Also, the first 500 bp of the 16S rRNA gene is identical between pairs of M. marinum-M. ulcerans (51), M. abscessus-M. chelonae, and M. vaccae-M. vanbaalenii (11) isolates.…”
mentioning
confidence: 93%